METHODS FOR ELIMINATING SPEECH DEFECTS IN CHILDREN OF JUNIOR SCHOOL AGE - Karlibayeva Juldiz Amangeldi kizi; Shakirova Salima (Galaxy International Interdisciplinary Research Journal, 2021)
The period of junior school age of children is from the age of 7 to the age of 11 years of study in primary classes. The childhood period in the kindergarten age is over. Before coming to school, the child will be physically and psychologically ready to receive education, in other words, to fulfill the various requirements imposed on the side of the most important period of his life, that is, the school period, according to the following. The vocabulary room of the 7 young child is also rich enough and the amount of concepts mavhum is much higher. The child understands what he hears, wide enough. As it turned out from the research of specialists, well-organized education develops the thinking of children from the age of 6 to the age of 7 years. They will be able to draw up and eat simple exercises and issues. The feeling of duty and responsibility in them begins to wane. A 7-year-old child will have experience in managing his / her emotions, all of which are acceptable to the principles of obhektiv that the child is ready in terms of school psychology, one of the important conditions in the preparation for school education is all that he / she said above. In the organization of pedagogical work in primary classes, it is necessary to take into account the level of social development of anatomical physiological characteristics of children of small school age. In this article, we will focus on the methods for eliminating speech defects in children of junior school age.